2023
DOI: 10.3389/fimmu.2023.1122972
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of fibrosis, kidney tissue injury and inflammation may predict severity and outcome of renal ANCA – associated vasculitis

Abstract: BackgroundActivity and chronicity of kidney involvement in ANCA-associated vasculitis (AAV) can be currently reliably evaluated only by kidney biopsy. In this study, we measured a panel of serum and urinary biomarkers collected at the time of kidney biopsy and hypothesized that they could reflect specific histopathological parameters in the biopsy and help to predict prognosis.MethodsWe examined a cohort of 45 patients with AAV and 10 healthy controls. Biomarker levels (DKK-3, CD163, EGF, PRO-C6 and C3M) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Outliers were defined as values deviating >2 SD from the mean of the log 2 24-h urinary endotrophin excretion. 27 Furthermore, since urinary endotrophin has been shown to reflect the degree of fibrosis in nontransplant patients with kidney disease, 14,15 we reevaluated the association of 24-h urinary endotrophin excretion with study endpoints after excluding KTR with recurrent kidney disease as the cause of graft failure. Next to that, we repeated the Cox regression analyses with urinary endotrophin concentration and urinary endotrophin concentration indexed for creatinine (urinary endotrophin/creatinine ratio).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outliers were defined as values deviating >2 SD from the mean of the log 2 24-h urinary endotrophin excretion. 27 Furthermore, since urinary endotrophin has been shown to reflect the degree of fibrosis in nontransplant patients with kidney disease, 14,15 we reevaluated the association of 24-h urinary endotrophin excretion with study endpoints after excluding KTR with recurrent kidney disease as the cause of graft failure. Next to that, we repeated the Cox regression analyses with urinary endotrophin concentration and urinary endotrophin concentration indexed for creatinine (urinary endotrophin/creatinine ratio).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, urinary endotrophin has been shown to reflect the degree of kidney fibrosis in patients with IgA nephropathy and ANCA-associated vasculitis, 14,15 and it can also be used as a prognostic marker to identify patients with a higher risk of worse kidney function. 15,16 Furthermore, urinary endotrophin has also been shown to be associated with disease progression in patients with chronic kidney disease (CKD). 12 In the KTR population, a recent study reported that urinary endotrophin at 3 mo posttransplantation was associated with lower kidney function at 12 mo.…”
mentioning
confidence: 99%
“…However, biopsy may not always be feasible or may carry risks. In a pilot study by Satrapova et al urinary levels of five inflammation and kidney fibrosis biomarkers were collected from 45 AAV patients with renal involvement at biopsy (76). DKK-3 and PRO-C6 levels predicted renal fibrosis extent, peaking in the sclerotic class and lowest in the focal class, while C3M was higher in focal classes (76).…”
Section: Clinical Features and Treatment Updatementioning
confidence: 99%
“…In a pilot study by Satrapova et al urinary levels of five inflammation and kidney fibrosis biomarkers were collected from 45 AAV patients with renal involvement at biopsy (76). DKK-3 and PRO-C6 levels predicted renal fibrosis extent, peaking in the sclerotic class and lowest in the focal class, while C3M was higher in focal classes (76). These biomarkers correlated with renal function at follow-up; higher DKK-3 and PRO-C6 levels were associated with worse renal function, while higher C3M levels correlated with better function.…”
Section: Clinical Features and Treatment Updatementioning
confidence: 99%
See 1 more Smart Citation